2019
DOI: 10.1111/scd.12414
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 0.2% chlorhexidine gel on oral health and the incidence of pneumonia amongst adults with profound complex neurodisability

Abstract: Aims: Investigate the effect of toothbrushing with 0.2% chlorhexidine gel on oral health and pneumonia amongst patients with a neurodisability who are fed via percutaneous endoscopic gastrostomy. Method:Forty-nine patients at the Royal Hospital for Neuro-disability were recruited to an observational study. Daily toothbrushing with 0.2% chlorhexidine gel was undertaken for 12 months by trained nursing staff. Plaque and gingival health were assessed every six weeks using the Simplified Debris Index and the Basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, as stated by Prasad et al 24 (2009), it is difficult to ascertain whether the significant improvement in oral hygiene found in their study was due to chlorhexidine use or the improved technique of the ward staff or, indeed, both factors combined.…”
Section: Discussionmentioning
confidence: 75%
“…However, as stated by Prasad et al 24 (2009), it is difficult to ascertain whether the significant improvement in oral hygiene found in their study was due to chlorhexidine use or the improved technique of the ward staff or, indeed, both factors combined.…”
Section: Discussionmentioning
confidence: 75%
“…For example, De Rossi and Glick 14 suggested considering 0.12 chlorhexidine mouthwash before dental procedures as this may help to reduce the risk of pneumonia. However, recent evidence found that daily tooth brushing with 0.2% chlorhexidine was effective in improving oral health but did not significantly affect the annual rates of pneumonia 30 …”
Section: Discussionmentioning
confidence: 98%
“…However, recent evidence found that daily tooth brushing with 0.2% chlorhexidine was effective in improving oral health but did not significantly affect the annual rates of pneumonia. 30 Only one review identified recommended antibiotic prophylaxis before dental extraction for people with splenic dysfunction, splenectomy or congenital asplenia but offered no conclusion regarding the actual need and effectiveness of antibiotic prophylaxis. Terezhalmy and Hall 26 supported prescribing antimicrobial agents before dental procedures that may induce bacteraemia to reduce the risk of sepsis due to the lack of evidence regarding the proper dental management of people with splenic dysfunction, splenectomy or congenital asplenia.…”
Section: Country Aims Recommendationsmentioning
confidence: 99%